B(Ml) and (I1 II f - Al-Alawy, I.T.; lbraheim, K. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In   the   present    work    the    nuclear    structure   of   even-evenBa(A=130-136,   Z=56)  isotopes   was  studied   using  (IBM-1).  The reduced matrix  element of magnetic dipole moment  (11  II f(Ml) II/,) and the magnetic dipole transitions probability B(M 1) were calculatedfor one and two bodies of even-even Ba(A=lJ0-136, Z=56). A goodagreement had been found of present with available experimental  data.